Combined use of a videolaryngoscope and a flexible bronchoscope for awake tracheal intubation when front‐of‐neck airway is not an option. Issue 1 (13th January 2021) - Khan, M. F.; Shamim, F.; Slote, M. U.; Salim, B.; Abbas, S. A.
Summary: We report a case of successful tracheal intubation with the combined use of a videolaryngoscope and flexible bronchoscope in a patient with difficult airway when both techniques had individually failed. A 35‐year‐old man presented with airway obstruction due to massive neck swelling causing hypoxia, stridor and respiratory distress. He had a history of oral cancer which had been resected with bilateral neck dissection and free flap reconstruction 2 months previously. Due to extensive anterior neck swelling, we judged that front‐of‐neck airway would not be a suitable approach. After unsuccessful attempts at awake tracheal intubation with videolaryngoscopy and flexible bronchoscopy separately, we combined both techniques with a successful outcome. By using a combined technique to address the specific problems presented by this case, a life‐threatening emergency was resolved. This case highlights why it is useful for anaesthetists to be familiar with multiple techniques to awake tracheal intubation, both individually and in combination.